Exploring The Role Of Code-Switching In Bilingual Classroom Interactions - Juhairi, Iman; Sudrajad, Wahyu (LP3M Universitas Islam Zainul Hasan Genggong, 2022)
This study explores the role of code-switching in bilingual classroom interactions, focusing on how switching between languages facilitates learning, social interaction, and cultural expression. Code-switching, the practice of alternating between languages within a conversation, is a common phenomenon in bilingual classrooms and serves multiple functions, including clarifying instructions, managing classroom discipline, and reinforcing identity. This research employs a qualitative approach, analyzing interactions within bilingual classrooms through recorded observations and interviews with students and teachers. Findings reveal that code-switching serves as a strategic tool for enhancing comprehension and engagement, enabling students to navigate complex linguistic and cultural contexts. Moreover, it supports peer collaboration and fosters an inclusive learning environment by validating students’ bilingual identities. By examining the pedagogical implications of code-switching, this study provides insights for educators in bilingual settings, highlighting the potential of code-switching to enrich both language acquisition and classroom dynamics.